Усмотрение в налоговом правоприменении - Старых Юлия Васильевна (Юриспруденция, 2007)
Экземпляры: аб. (2008) / Инвентарный номер: 51857 / Цена: / Сис.шифр: 67.402 / Авт.знак: С 77 / ГРНТИ: 10.21.63 / ББК: 67.402